2018
DOI: 10.3892/mmr.2018.9417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Panax ginseng C.A. Meyer extract on the offspring of adult mice with maternal immune activation

Abstract: To understand maternal immune activation (MIA) during prenatal development, the synthetic double-stranded RNA polyriboinosinic-polyribocytidylic acid [poly(I:C)] has been widely used in animal models to induce behavioral deficits similar to those in schizophrenia and other psychotic disorders. Panax ginseng C.A. Meyer (PG) extract is widely used to treat various kinds of nervous system disorders in Asia particularly China and Korea. The present study aimed to examine the effects of PG extract on MIA offspring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…In our study, in the adult males exposed to Poly I:C, the social interactions were shifted towards enhanced aggressive behaviour. Similarly, experimental data from animal models wherein Poly I:C was administrated to pregnant mice have highlighted the presence of an aggressive phenotype in adult offspring [ 110 , 111 ]. Therefore, the diminished hippocampal CX3CR1 level, which we observed in prenatally Poly I:C-treated young offspring, opens the possibility that disruptions of microglia-mediated activity could contribute to neurodevelopmental deficits manifested as behavioural schizophrenia-like changes in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, in the adult males exposed to Poly I:C, the social interactions were shifted towards enhanced aggressive behaviour. Similarly, experimental data from animal models wherein Poly I:C was administrated to pregnant mice have highlighted the presence of an aggressive phenotype in adult offspring [ 110 , 111 ]. Therefore, the diminished hippocampal CX3CR1 level, which we observed in prenatally Poly I:C-treated young offspring, opens the possibility that disruptions of microglia-mediated activity could contribute to neurodevelopmental deficits manifested as behavioural schizophrenia-like changes in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the results obtained in Wistar offspring rats conducted in the same experimental setting showed that social interactions were shifted towards enhanced aggressive behaviour [ 73 ]. Also, in animal models wherein Poly I:C was administered to pregnant mice, an increase in the presence of an aggressive phenotype in adult offspring was highlighted [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AVGs were measured in the registration window of 200 ms. After 5 min of habituation with background noise, the animals were randomly subjected to four types of acoustic stimuli. Each experimental trial consisted of either a single pulse [intensity: 120 dB, duration: 40 ms, (P)] or a pulse preceded by a prepulse at one out of three intensities [70,75,80 At PND100, the offspring from the MIA group were divided into two categories: MIA PPI-low (with the deficit in PPI) and MIA PPI-high (without the deficit). The subcategorization was performed based on the PPI results calculated with the AVGs for the 75 dB prepulse.…”
Section: Prepulse Inhibition Testmentioning
confidence: 99%
“…Some HMs such as Chai Hu Shu Gan San and Xiao Yao San, which include Bupleuri Radix as a key component, have significant therapeutic effects on depression 70,78 . Other components of SGYMT, including Ginseng Radix , also have antidepressant effects 7981 . Moreover, the multiple components of HM may exert a complex effect on multiple molecular targets 23 .…”
Section: Discussionmentioning
confidence: 99%